Evolution of the hypercarnivorous dentition in mammals (Metatheria, Eutheria) and its bearing on the development of tribosphenic molars. Issue 2 (9th February 2017) - Solé, Floréal; Ladevèze, Sandrine
SUMMARY: One major innovation of mammals is the tribosphenic molar, characterized by the evolution of a neomorphic upper cusp (=protocone) and a lower basin (=talonid) that occlude and provide shearing and crushing functions. This type of molar is an evolutionarily flexible structure that enabled mammals to achieve complex dental adaptations. Among carnivorous mammals, hypercarnivory is a common trend that evolved several times among therians (marsupials, placentals, and stem relatives). Hypercarnivory involves an important simplification of the carnassial molar pattern from the ancestral tribosphenic molar pattern, with the modification of the triangular tooth crown, and the loss of several cusps and cuspids typical of the tribosphenic molar. These losses confer to the molars of the hypercarnivorous mammals a plesiomorphic/paedomorphic morphology that resembles more the earliest mammaliaforms than the earliest therians. Here, we demonstrate that the modification of the molar morphology is fully explained by a patterning cascade mode of cusp development. Contrary to what was previously proposed, our study concludes that the metaconid (mesiolingual cusp of lower molars, associated with a puncturing function) does not influence cusp development of the talonid (distal crushing heel of lower molars). Moreover, it provides a new example of how heterochronic changes were crucial to the evolution of mammal dentition. To overcome the difficulty of applying behavioral or ecological definitions of diets to fossil animals, we characterize hypercarnivorous dentitions on the basis of the molar morphology and more particularly on the loss or retention of crushing structures, each dentition resulting from adaptations to a distinct ecomorphotype. Despite repeated and convergent evolution of hypercarnivorous forms, hypercarnivory appears as a highly constrained specialization (i.e., "dead end") that is unlikely to evolve back to omnivorous dentition, especially when the crushing structures are lost.